1968
DOI: 10.3109/00016346809157466
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen, Progestogen and Liver‐function Tests

Abstract: When considering the reason for the abnormal liver-function tests in subjects to whom oral contraceptives have been administered it has been suggested that either the oestrogen or the progestogen component is responsible for the changes in these tests (Adlercreutz, 1964; Eisalo et al., 1964; Boake et nl., 1965; Stoll et al., 1966) or that a synergetic action of the two components takes place (Borglin, 1965; Eisalo et al., 1965).The present study concerns liver-function tests in subjects who have received synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1969
1969
1975
1975

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is possible that the combination of oestrogen and a progestagen, particularly a 19-nor compound, may increase their individual toxicity. Eisalo et al (1968) found this, lynoestrenol plus mestranol further impairing the liver function tests which had been altered by lynoestrenol alone. Alternatively the metabolism of 19-norprogestagens to the very active ethinyloestradiol (Brown & Blair, 1960) may fully explain the hepatic toxicity of progestagens.…”
Section: Progestagensmentioning
confidence: 80%
See 1 more Smart Citation
“…It is possible that the combination of oestrogen and a progestagen, particularly a 19-nor compound, may increase their individual toxicity. Eisalo et al (1968) found this, lynoestrenol plus mestranol further impairing the liver function tests which had been altered by lynoestrenol alone. Alternatively the metabolism of 19-norprogestagens to the very active ethinyloestradiol (Brown & Blair, 1960) may fully explain the hepatic toxicity of progestagens.…”
Section: Progestagensmentioning
confidence: 80%
“…There is some evidence that the similar but unsaturated substitution groups in the 17a-position in 19-norprogestagens do likewise, and Eisalo, Heino & Rasanen (1968), for example, have recently found that the 19-norprogestagen lynoestrenol induced more abnormal liver function tests than did the progestagen megestrol, which has a different structure. Kleiner et al (1965) suggested that progestagens are the hepatotoxic component of the pill, for they found that oestradiol (2-5 mg/day) for 10 days had no effect on the liver function of normal women, even on the BSP transport maxima.…”
Section: Progestagensmentioning
confidence: 99%
“…There are other differences in the effect of these two oestrogens on carbohydrate metabolism (Di Paola et al, 1968), liver function (Eisalo et al, 1968), and also vitamin B6 metabolism (Luhby et al, 1971). Clearly, further studies of a similar nature to this with a combined contraceptive formulation comprising ethinyl oestradiol instead of mestranol at a dose of 50 ug or even less and 1 mg of norethisterone will provide further interesting data, and these studies are under way.…”
Section: Discussionmentioning
confidence: 99%